Zakat disbursement via capital assistance: a case study of Majlis Agama Islam Johor / Ahmad Che Yaacob, Safiah Mohamed, Azizah Daut, et. all. - Mohamed, Safiah; Daut, Azizah; Ismail, Normah; Mohd Don, Mohd Ali (Faculty of Business and Management, 2013)
This paper examines management of zakat in the state of Johor and focuses on the distribution of zakat to the recipients of capital assistance who are involved in the socio-development programs. It intends to examine the impact of the program towards their achievements after receiving capital assistance to start their small business ventures. Both primary and secondary data are used in the studies. The primary data were collected from interviews with the officers of Majlis Agama Islam Johor (MAIJ) and the statistical data were obtained from documents such as reports, financial records, and brochures. The findings show commendable improvement in zakat management for the five-year period of study. Nonetheless, recommendations pertaining to supervision, procedures, and cooperation are posed for improving the programs in assisting the poor and needy recipients and to optimize the zakat disbursement. The study was made possible with the research grant from Accounting Research Institute (ARI) of UiTM.